THE EFFECT OF CAPITAL STRUCTURE ON CASH DIVIDEND POLICY WITH LIQUIDITY AS MODERATION IN MINING COMPANIES ON IDX 2015-2019 - Lissa Mariyana (Management Department, Faculty of Economics and Business, Universitas Jambi, 2021)
A company will be assessed for its resilience in surviving as an economy, one of them is a mining company that is required to have a stock of funds. This research involves mining companies, because the mining sector has experienced a decline and has had the lowest growth since 2013 until now. This occurs because the price of global mining commodities is experiencing a price decline following the decline in demand from China and other developing countries, as well as the existence of the Mineral and Coal Law policy which also suppresses the growth of the mining sector internally and has the potential to be a liquidity value for a company. This study will measure the capital structure through IOS, company size, growth rate, profitability, and business risk which affect the cash dividend policy with liquidity as a moderating variable in mining companies listed in 2015-2019. The research method used is to use associative quantitative with a sample of 41 mining sector companies listed on the Indonesia Stock Exchange during the 2015-2019 period.The type of data used in this study is secondary data which includes data from the financial statements of mining companies with analysis using descriptive statistics. The results of the research show that simultaneously, IOS, Company Size, Growth Rate, Profitability (ROI) and Business Risk have a significant effect on cash dividend policy (DEV) through liquidity moderation.